Eksplorasi Nilai Kearifan Lokal Sebagai Dasar Pengembangan Teori Kesantunan Berbahasa Indonesia - Pramujiono, Agung (Jurnal Budaya Nusantara, 2015)
The theory of Politeness in general oriented to the theory developed by western experts as Lakoff, Leech, Brown and Levinson, Arndt and Janncy, and Watts.